A Green Revolution in the West African cocoa belt - Bhattacharjee, Ranjana; Gockowski, J.; Asare, R.; Muilerman, Sander (2012)
STCP tools for the rehabilitation of West African cocoa farms Cacao tree stocks in West Africa are mainly established from seeds procured from farmers’ fields. This planting material lacks the disease tolerance and yield potential of the hybrid seed. Productivity is also affected by the old age of West Africa’s tree stock. Replacing and rehabilitating the tree stocks of West Africa is fundamental to the achievement and long-run sustainability of a cocoa Brown Revolution. The STCP has developed a Planting, Replanting and Diversification (PRD) training package to provide farmers the knowledge and technical skills needed to rehabilitate old cocoa farms or reclaim degraded areas using hybrids. However, a major constraint to hybrid adoption is a lack of access to hybrid seeds. To overcome this constraint, STCP introduced a Seed Brokerage System (SBS) for the collective acquisition of hybrid seeds by farmer field school groups from government production units. An initial evaluation of 375 randomly selected trainees revealed that the mean participant had successfully established 0.4 ha of hybrid cocoa seedling with an 81% seedling survival rate after two dry seasons. Approximately half of the surveyed trainees had replanted old farms while half had established new farms on degraded fallow land. The SBS also brokered timber seedlings for farmers desiring to include high-value timber (Terminalia ivorensis and T. superb) as permanent shade in their production system. The mean participant reported the successful establishment of 12 timber seedlings which is equivalent to 30 trees per hectare. Farmers favored the SBS innovation and are seeking its continuance.